Autoinducer-2 of Streptococcus mitis as a Target Molecule to Inhibit Pathogenic Multi-Species Biofilm Formation In Vitro and in an Endotracheal Intubation Rat Model - Wang, Zhengli; Xiang, Qingqing; Yang, Ting; Li, Luquan; Yang, Jingli; Li, Hongong; He, Yu; Zhang, Yunhui; Lu, Qi; Yu, Jialin (Frontiers in Microbiology, 2016)
Abstract Streptococcus mitis (S. mitis) and Pseudomonas aeruginosa (P. aeruginosa) are typically found in the upper respiratory tract of infants. We previously found that P. aeruginosa and S. mitis were two of the most common bacteria in biofilms on newborns’ endotracheal tubes (ETTs) and in their sputa and that S. mitis was able to produce autoinducer-2 (AI-2), but P. aeruginosa was not. Recently, we also found that exogenous AI-2 and S. mitis could influence the behaviors of P. aeruginosa. We hypothesized that S. mitis contributes to this interspecies interaction and that inhibition of AI-2 could result in inhibition of these effects. To test this hypothesis, we selected PAO1 as a representative model strain of P. aeruginosa and evaluated the effect of S. mitis as well as an AI-2 analog (D-ribose) on mono- and co-culture biofilms in both in vitro and in vivo models. In this context, S. mitis promoted PAO1 biofilm formation and pathogenicity. Dual-species (PAO1 and S. mitis) biofilms exhibited higher expression of quorum sensing genes than single-species (PAO1) biofilms did. Additionally, ETTs covered in dual-species biofilms increased the mortality rate and aggravated lung infection compared with ETTs covered in mono-species biofilms in an endotracheal intubation rat model, all of which was inhibited by D-ribose. Our results demonstrated that S. mitis AI-2 plays an important role in interspecies interactions with PAO1 and may be a target for inhibition of biofilm formation and infection in ventilator-associated pneumonia.